Sebaran dan Kemelimpahan Burung Layang-Layang Asia (Hirundo rustica Linn.) di Propinsi Daerah Istimewa Yogyakarta - W, Stefan Agung; Djuwantoko, Djuwantoko; Jati, Wibowo N. (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2005)
Asian Swallow Bird (Hirundo rustica Linn.) representing one of the type of bird migran which is spread over in almost entire all earth. This Bird type in Java and Bali represent the common winter visitor met in all height. Information of concerning this animal existence in Yogyakarta very minim, last data about existence and amount of Asian swallow bird population in Yogyakarta in reporting in the year 1996 and till now there is no researcher reporting the species existence in Yogyakarta. This Research study about abundance population and distribution Asian swallow bird at season of migration of September 2003 - March 2004 in all region Yogyakarta. Research conducted in all region of Province of Special Region of Yogyakarta consisted by 5 sub-province, that is Sub-Province Sleman, Sub-Province Bantul, Sub-Province Kulonprogo, Sub-Province of Gunung Kidul and Municipality D.I. Yogyakarta. Parameter measured in this research is estimating an abudan of population and location of distribution population. Data intake of is amount of population conducted by direct enumeration, whereas intake of distribution data conducted by noting the name of location and geographical position. Data of result of research obtained in compiling in tables, is later then made by graph of population fluctuation and ploted in map of pursuant to co-ordinate finding of Asian swallow bird individual. To know diffraction resulted by a population enumeration, will be counted with the standard deviation formula. Result of perception indicate that full scale of Asian swallow bird population during a period to migration reach the maximum value equal to 32.579 that happened at third week of November 2003 and amount of biggest population is concentration in jl. K.H. Ahmad Dahlan and jl. Senopati, area Malioboro, Municipality Yogyakarta, that is equal to 28877ï‚± 36,91. Sub-Province Bantul represent the area which is at most met by the Asian swallow bird location.